Can an emergency department clinical "triggers" program based on abnormal vital signs improve patient outcomes?. Issue 4 (13th September 2016) - Imperato, Jason; Mehegan, Tyler; Henning, Daniel J.; Patrick, John; Bushey, Chase; Setnik, Gary; Sanchez, Leon D.
Abstract: Background: Because abnormal vital signs indicate the potential for clinical deterioration, it is logical to make emergency physicians immediately aware of those patients who present with abnormal vital signs. Objectives: To determine if a clinical triggers program in the emergency department (ED) setting that utilized predetermined abnormal vital signs to activate a rapid assessment by an emergency physician-led multidisciplinary team had a measurable effect on inpatient hospital metrics. Methods: The study design was a retrospective pre and post intervention study. The intervention was the implementation of an ED clinical "triggers" program. Abnormal vital sign criteria that warranted a trigger response included: heart rate <40 beats/minute or>130 beats/minutes, respiratory rate <8 breaths/minute or>30 breaths/minute, systolic blood pressure <90 mm Hg, or oxygen saturation <90% on room air. The primary outcome investigated was the median days admitted with secondary outcomes of median days in special care unit, in-hospital 30-day mortality and proportion of patients who required an upgrade in inpatient care level. Results: There was no difference in median days admitted for inpatient care (3.8 v. 4.0 days, p =0.21) or median days spent in a special care unit (5.0 v. 5.6 days, p =0.42) between the groups. There was no difference in the percentage of in-hospital patient deaths (6.0% v. 5.6%, p =0.66) or frequency of upgrade in level of care within 24 hours (4.9% v. 4.0%, p =0.52). Conclusions: In our study, the implementation of an ED clinical triggers program did not result in a significant change in measured inpatient outcomes. Résumé: Contexte: Comme des signes vitaux anormaux peuvent être annonciateurs d'une détérioration clinique, il est logique d'informer immédiatement les médecins d'urgence de l'état des patients qui ont des signes vitaux anormaux. Objectif: L'étude visait à déterminer si un programme de « déclencheurs » cliniques au service des urgences (SU) reposant sur la présence de signes vitaux anormaux prédéterminés, mis en œuvre afin de permettre une évaluation rapide des malades visés par une équipe pluridisciplinaire sous la conduite d'un médecin d'urgence pouvait se traduire par un effet mesurable sur des critères de mesure chez les malades hospitalisés. Méthode: Il s'agit d'une étude rétrospective, à échantillons distincts, de type avant et après une intervention, suivant la mise en œuvre d'un programme de déclencheurs au SU. Étaient considérés comme des critères de signes vitaux anormaux justifiant la mise en branle du programme une fréquence cardiaque <40 ou>130 battements/min, une fréquence respiratoire <8 ou>30 cycles/min, une pression systolique < 90 mm Hg ou une saturation en oxygène <90 % à l'air ambiant. Le principal critère d'évaluation était le nombre médian de jours d'hospitalisation, et les critères d'évaluation secondaires consistaient en le nombre médian de jours passés dans un service de soins spécialisés, en la mortalité hospitalière au bout de 30 jours et en la proportion de patients dont l'état avait nécessité un relèvement du niveau de soins durant le séjour à l'hôpital. Résultats: Aucun écart n'a été enregistré entre les groupes en qui concerne le nombre médian de jours d'hospitalisation (3, 8 contre [c.] 4, 0 jours; p =0, 21) ou le nombre médian de jours passés dans un service de soins spécialisés (5, 0 c. 5, 6 jours; p =0, 42). Il n'y avait pas de différence non plus quant au pourcentage de la mortalité hospitalière (6, 0 % c. 5, 6 %; p =0, 66) ou à la fréquence du relèvement du niveau de soins en 24 heures (4, 9 % c. 4, 0 %; p =0, 52). Conclusion: Dans le modèle présenté ici, la mise en œuvre d'un programme de déclencheurs au SU ne s'est pas traduite par des changements importants de résultats cliniques mesurés chez les malades hospitalisés.